Staging Parkinson’s Disease Combining Motor and Nonmotor Symptoms Correlates with Disability and Quality of Life - D. Santos García; T. De Deus Fonticoba; J. M. Paz González; C. Cores Bartolomé; L. Valdés Aymerich; J. G. Muñoz Enríquez; E. Suárez; S. Jesús; M. Aguilar; P. Pastor; L. L. Planellas; M. Cosgaya; et al. (Parkinson's Disease)
Introduction. In a degenerative disorder such as Parkinson’s disease (PD), it is important to establish clinical stages that allow to know the course of the disease. Our aim was to analyze whether a scale combining Hoehn and Yahr’s motor stage (H&Y) and the nonmotor symptoms burden (NMSB) (assessed by the nonmotor symptoms scale (NMSS)) provides information about the disability and the patient’s quality of life (QoL) with regard to a defined clinical stage. Materials and Methods. Cross-sectional study in which 603 PD patients from the COPPADIS cohort were classified according to H&Y (1, stage I; 2, stage II; 3, stage III; 4, stage IV/V) and NMSB (A: NMSS = 0–20; B: NMSS = 21–40; C: NMSS = 41–70; D: NMSS ≥ 71) in 16 stages (HY.NMSB, from 1A to 4D). QoL was assessed with the PDQ-39SI, PQ-10, and EUROHIS-QOL8 and disability with the Schwab&England ADL (Activities of Daily Living) scale. Results. A worse QoL and greater disability were observed at a higher stage of H&Y and NMSB (p<0.0001). Combining both (HY.NMSB), patients in stages 1C and 1D and 2C and 2D had significantly worse QoL and/or less autonomy for ADL than those in stages 2A and 2B and 3A and 3B, respectively (p<0.005; e.g., PDQ-39SI in 1D [n = 15] vs 2A [n = 101]: 28.6 ± 17.1 vs 7.9 ± 5.8; p<0.0001). Conclusion. The HY.NMSB scale is simple and reflects the degree of patient involvement more accurately than the H&Y. Patients with a lower H&Y stage may be more affected if they have a greater NMS burden.